Um índice de governança para empresas no Brasil - Laise Ferraz Correia (2008)
The purpose of this thesis was to develop a governance index for Brazilian companies. This index encompasses a set of mechanisms implemented in firms to reduce agency problems. It was then validated on a sample of companies listed on São Paulo Stock Exchange between1997 and 2006. To build the governance index we bring into play the agency perspective of corporate governance and by consequence its viewpoint concerning firms efficiency. In this approach, good governance consists of mechanisms designed to assure suppliers of capital that they will be given back the return on their investment. Thus, the corporate governance index comprises control and alignment mechanisms that are put into practice in order to align managers and shareholders interests or the ones of majority and minority shareholders, which are pointed out by agency theory and her empirical evidence. The five governance dimensions considered are board of directors composition, ownership structure, managers compensation, protection of minority shareholders, and transparency (disclosure). In carrying on the empirical analysis, we first analyzed each dimension in isolation and taking their interrelations into account in a panel data framework as well. Second, we developed the quality of governance index by means of the principal components multivariate technique. Actually, the index was constructed as a weighted average of all components generated in this procedure, where the weights are given by their respective variances (eigenvalues). The analysis of our index exhibited an effective accrue in the governance levels of the analyzed Brazilian companies. In terms of external validation, the index was faced to indicators of the financial investors trust on a company. The results revealed that stock liquidity, stock price, and market capitalization increase significantly through the governance index quintiles built in ascending order of governance quality. In his own way, the book-to-market ratio decreases through the governance index quintiles, implying that growing firms have better governance levels. In general, the analysis showed that stocks from better governed firms are more attractive to investors. Finally, we carried out a panel data analysis of the relationship between firms financial performance and the corporate governance index. We find a positive and significant relationship between Tobins Q and the quality of governance index. Therefore, we find support for the hypothesis of a positive link between good governance and firm value. Better, we also document an inverse relationship between the corporate governance index and the risk-adjusted stock return, suggesting that investors require a higher rate of return from firms which present worse governance levels. All of these relationships give evidence that financial investors trust on a company strongly relates to the governance quality expressed by the index. Therefore, the empirical analysis validates in a great measure the corporate governance index proposed. Investors are ready to pay higher prices to stocks from better governed companies, mainly because the likelihood of getting their investiment back is higher under these circumstances. Lastly, we conclude from the empirical evidence reported in this thesis that good governance has a value to the market.